DNA barcoding as a tool for detecting mislabeling of fishery products imported from third countries: An official survey conducted at the Border Inspection Post of Livorno-Pisa (Italy). (October 2017) - Guardone, L.; Tinacci, L.; Costanzo, F.; Azzarelli, D.; D'Amico, P.; Tasselli, G.; Magni, A.; Guidi, A.; Nucera, D.; Armani, A.
Abstract: The importation of fishery products into the European Union (EU) is constantly rising. The aim of this study was to conduct a survey on labeling non-compliances on fishery products imported from extra-European countries, in collaboration with the veterinary staff of the Border Inspection Post of Livorno-Pisa (BIP), of the Italian Ministry of Health. The correspondence between the products' identity and the scientific denominations reported on the accompanying certificates was checked using the DNA barcoding method. Overall, 277 products belonging to different categories (fish, cephalopods, crustaceans, bivalves, amphibian) were submitted to analysis for species identification. The comparison of the molecular results with the scientific names declared on the accompanying documents showed that 22.5% (95%CI 17.8–28.0) of the analyzed products were mislabeled. The highest percentage of mislabeling was observed on cephalopod based products (43.8%, 95% CI 32.3–55.9), followed by crustaceans (17.0%, 95% CI 9.2–29.2) and fish (14.0%, 95% CI 8.7–21.9). A higher rate was found in products imported from China, Vietnam and Thailand. The present study is the first survey on mislabeling in products sampled at BIPs in Italy. The results highlight the need of implementing analytical checks, based on DNA analysis, on incoming fishery products. Highlights: Food of animal origin from an extra-EU country must undergo veterinary border controls. A survey on labeling non-compliances on 277 imported fishery products was conducted. Sampling was performed at the Border Inspection Post of Livorno-Pisa. The overall mislabeling rate was 22.5%. The highest percentage was found for cephalopods. Analytical checks, based on DNA barcoding, on incoming fishery products are needed.